Simple Iterative trilateration-based scheme for indoor localization of IoT devices - Risteska Stojkoska, Biljana; Jofce, Nasi (My University, 2017)
Indoor localization, as a key enabling technology for Internet of Things (IoT) location-based applications, is one of the primary services in smart automated systems. It is becoming increasingly important and beneficial in many industrial, commercial and public domains. This paper proposes an iterative trilateration technique for localization in indoor IoT environment, as an improvement of baseline trilateration. In our simulations, the iterative trilateration achieves high localization coverage with accurate location estimation compared to baseline trilateration. Additionally, our technique was analyzed considering different parameters like communication range, range error and anchors’ fraction in three-dimensional (3D) space under scenarios with and without obstacle. The results show that our iterative trilateration technique is almost resistant to the obstacles in the environment.
Keywords: Internet of Things, indoor localization, iterative trilateration, obstacle